TENS Alleviates Muscle Weakness Attributable to Attenuation of Ia Afferents - Konishi, Y.; McNair, P. J.; Rice, D. A. (International Journal of Sports Medicine, 2017)
Quadriceps weakness is a notable problem following knee damage. Research has shown effectiveness of TENS in improving Quadriceps weakness associated with arthrogenic muscle inhibition. However, these studies were not focused upon short term delivery of TENS, nor did they examine the potential mechanism(s). The present study examined the effect of 25–30 s of TENS upon weakness induced temporarily by a prolonged vibration. Subjects performed eccentric MVCs under 2 conditions (TENS and no-TENS). First, MVC was measured at baseline. For the TENS condition, TENS was applied to each subject’s knee joint during a second MVC measurement after vibration. For no-TENS condition, TENS was not applied during the 2nd MVC measurement. MVC between pre-and post-vibration stimulation were compared across the 2 conditions. The results showed that MVC and EMG of TENS-condition was larger than that of no-TENS condition. Our results suggest that TENS could partially restore α-motoneuron activation, despite the induced dysfunctional γ-loop. These results suggest that mechanisms independent of the γ-loop such as a direct facilitation of the QF α-motoneuron pool by a long latency spinal-reflex and/or supraspinal mechanisms appear more likely to be responsible. The findings provide further support for utilizing TENS, even when γ-loop dysfunction is present following joint damage.
Keywords: TENS; AMI; gamma motor neuron; ACL; osteoarthritis; knee